Single-Photon Emission Computed Tomography with {199}Tl in Diagnostics of Malignant Tumors of the Larynx and Laryngopharynx; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Zelchan R. V. Roman Vladimirovich; Chernov V. I. Vladimir Ivanovich; Titskaya А. А. Anna Aleksndrovna; Sinilkin I. G. Ivan Gennadjevich; Chizhevskaya S.; Choynzonov E. T. (Radiation Technologies in Medicine, 2015)
Title screen